What makes nanotechnologies applied to agriculture green? - Bartolucci, Cecilia; Scognamiglio, Viviana; Antonacci, Amina; Fraceto, Leonardo Fernandes [UNESP] (Elsevier, 2022)
We describe a circular framework, divided into segments addressing specific aspects of potentially green interventions, that allows for a quick assessment of what makes nanotechnologies applied to agriculture green.
Keywords: Agriculture; Circular framework; Green agro-nanotechnologies; Sustainability